Pyrolysis -- a process to "melt" biomass - Klug, Michael (2012)
Pyrolysis is a thermochemical process that occurs in absence of oxygen. The pyrolysis process has three stages: feeding and dosing of raw materials, transformation of the organic mass and, finally, collection and separation of the products (coke, oil and gas). The pilot plant of the PUCP can produce second generation biofuels from organic waste and this responds to the challenge of a sustainable developmentof bioenergy in Peru.